Fabrication of Cordierite Ceramic Foam Filter by Replication Method - Ria Julyana Manullang; Maulid purnawan; Dede Taufik; Ayu Ratnasari; Karlina Noordiningsih (Jurnal Keramik dan Gelas Indonesia, 2021)
Ceramic foam filter (CFF) is widely used to improve the   quality   of   molten   metal   prior   to   casting. Cordierite  is  one  of  the  most  commonly  used materials  for making CFF. In this  research,  the fabrication of cordierite-based   CFF   by   a   replication   method   using   a polyurethane template has been studied. Waterglass and polymethacrylic acid (PMAA) were used as defloculants to synthesize ceramic  suspensions. CFF was made from kaolin, talc, alumina with a defloculant concentration of 0.3% which is sintered at a temperature of 1300 - 1350oC. The experimental results  showed that the porosity obtained for all CFF samples were  above  70%.  The  best  shape  of  CFF  was  obtained  by using PMAA as  defloculant. However, CFF did not reach the maximum  strength yet so it is necessary to carry out further research on the CFF body composition.